Pengaruh Sistem Pengendalian Internal dan Kejelasan Sasaran Anggaran terhadap Kinerja Manajerial: Studi Empiris pada Satuan Kerja Perangkat Daerah Kabupaten Karimun - Reza Pridima Putri; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2022)
The purpose of this study was to examine the effect of the internal control system and the clarity of budget targets on managerial performance. The population in this study is the regional work unit in Karimun Regency, totaling 27 SKPD, and Respondents in this study were the head of the office, secretary and head of the field at the SKPD. The type of research used in this study is a quantitative approach using primary data. Primary data was obtained by distributing questionnaires directly to 81 respondents. The data was then analyzed using multiple linear regression techniques. The results of this study are (1) the internal control system has a positive effect on managerial performance in the Karimun Regency Regional Apparatus Work Unit (SKPD), (2) the clarity of budget targets has a positive effect on managerial performance in the Karimun Regency Regional Apparatus Work Unit (SKPD).